The psychological impact of the Coronavirus emergency on physicians and nurses: an Italian observational study - Carriero, Maria Chiara; Conte, Luana; Calignano, Marica; Lupo, Roberto; Calabrò, Antonino; Santoro, Pietro; Artioli, Giovanna; Caldararo, Cosimo; Ercolani, Maurizio; Carvello, Maicol; Leo, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Background. The Coronavirus has put a strain on the response capacity of health systems and there are various psychological effects on health workers.Aim of the study. To investigate the psychological impact of the coronavirus emergency on physicians and nurses.Materials and methods. A study was conducted on a sample of nurses and physicians (n=770), who were asked to fill in a questionnaire investigating physical and psychological problems. It also included the IES (Impact Event Scale), STAI (State Trait Anxiety Inventory) scale and BDI (Beck Depression Inventory).Results. 87.7% of the sample was represented by nurses (n=675), 12.3% (n=95) by physicians. 52.3% (n=403) of the participants believed that they had not received good training on the correct use of Personal Protective Equipment. 18.2% (n=140) declared that they had experienced a moment in which they had had to choose among the patients whom to treat for an essential therapy. Among the psychological symptoms, stress (76.2%; n=587), anxiety (59.4%; n=457) and depression (11.8%) prevailed and only 3.9% of the healthcare personnel sought help from a psychologist. The total score of the IES-R scale was 3.47. A significant association emerged between exposure and the risk of contagion (p-value = 0.003), stress was more present among nurses than among physicians (77.5% vs. 67.4%; p = 0.003). Among physical symptoms, headache (52.2%; n=402) and pressure injuries (24.8% n= 191) prevailed.Conclusions. The results of the study show that mental health monitoring of health workers, who are at risk of developing major psychological disorders, is a priority.